If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + -13 = -5 Reorder the terms: -13 + c = -5 Solving -13 + c = -5 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + c = -5 + 13 Combine like terms: -13 + 13 = 0 0 + c = -5 + 13 c = -5 + 13 Combine like terms: -5 + 13 = 8 c = 8 Simplifying c = 8
| x^2(4e^2x)+4x(2e^2x)-18(e^2x)=0 | | 1.8z-0.8z+7.4=-6.6 | | 7v+7.8= | | 0.1=9h | | X^4-9x^2+2=0 | | -8+(-1)= | | -8=-3(5-2x)+1 | | 2(3x-4)=8+2x+4 | | 4.3-1.4(p+7)=-9 | | 3z+3=15 | | 0.30x+0.30(40)=0.15(130) | | 3y-y=5 | | -2(1)-4(1.5)=6 | | 3(x+2)=-18+9x | | 10t+10.3= | | 3(10+6x)=84 | | (xy-x)dx+(xy+y)dy=0 | | (35x-35)(25x-40)=0 | | 11+5v+3v^2=0 | | -6u=48 | | 4y=-4.4 | | -5x=8+y | | 2x=12+2h | | 4n+4.2= | | -3u=60 | | 2x+(x-2)=10 | | -2x-9x+33=-7 | | -17-9x=-10(1+x) | | 4m=122 | | 4(-9+x)=-12 | | 60^3/12x=0 | | X^2+54+728=0 |